As emissoras estatais de rádio e a radiodifusão de serviço público - Estudo de caso sobre as emissoras rádio vinculadas ao poder executivo no Brasil - Mingo, Ivana Sonegheti de (2021)
This dissertation intends to, through the perspective of public broadcasters, understand how the radios linked to the executive state powers affiliate themselves to a public communication service, a democratic practice allied to the commitment that must be assured by the state. Given the neoliberal territoriality that permeates the power relations and surrounds the current historical block, a hypothesis is proposed in which, covered by the chase for profit, financial or symbolic, the information production would attend the private, political or business interests, distancing itself from the democratic proposition that guarantees information as a right. Therefore this is a study on multiple cases to understand the practices of public state broadcasters. With the intention of proposing a parameter base for the public broadcasting, a bibliographic study was made about the subject, the results were compared to the public broadcasting developed in the american, british and canadian liberal democracies, which, beyond contributing to sustain global public broadcasting also kept themselves regulated even after the global capitalist advance of the deregulation movement. This information was then compared to the brazilian federal government public broadcasting practices, by means of the brazilian communication company, with the intention of comprehending which of those ideal characteristics were kept in the nacional communication public policies context. By observing the practices and principles of these public broadcasters, it was possible the development of tools for analyzing comparatively the brazilian state broadcasters. The analysis, based on the theoretical methodological axis of the Political Communication Economics, concludes that the state broadcasters lack financial and administrative independence in regard to the local executive powers. Despite that, and despite not having a clear legislation regarding the objectives to be pursued, there are, in some cases, the goal, promoted by regional movements, of broadening the participation mechanisms in the broadcasters, designing a communication proposition that envisions the democratization of information, making it plural end more diverse.